South—South Regional Financial Arrangements
XXVIII, 361 p. 31 illus., 28 illus. in color.
Keywords: This book shows how regional cooperation and integration have increased massively in scale and scope in recent years, as developing countries seek new ways to shield themselves from economic turbulence and to kick-start their economies in the face of stagnant global demand. The trend is partly a defense mechanism against the limitations of the international financial system, but also reflects a wider search for new and different growth paths more appropriate with developing countries’ increasing economic and political voice. As a consequence, the landscape of financial and monetary mechanisms has changed dramatically, especially in the ten years since the economic crisis of 2007–2008. Diana Barrowclough is a Senior Economist in the United Nations Conference for Trade and Development, Division on Globalization and Development Strategies. Richard Kozul-Wright is Director of the Globalisation and Development Strategies Division in UNCTAD. William N. Kring is the Assistant Director of the Global Development Policy Center, a university-wide center housed at the Frederick S. Pardee School for Global Studies. Kevin P. Gallagher is a Professor of global development policy at the Frederick S. Pardee School of Global Studies and the Director of the Global Development Policy Center (GDPC). .